115k views
1 vote
What is the term to term rule: 1, -6, -13, -20, -27, -34

User Tim Siwula
by
5.3k points

2 Answers

3 votes

Answer:

The term-to-term rule for the sequence 1, -6, -13, -20, -27, -34 is...

YOU TAKE AWAY 7 TO GET THE NEXT NUMBER!

Explanation:

i.e. 1 - 7 = -6, -6 - 7 = -13 and so on...

In other words, the formula is -7n+8

HOPE THIS HELPS!

User Ivan Manzhos
by
5.1k points
5 votes

Answer:

Explanation:

Term 2 - term 1 = -6 - 1 = -7

Difference = -7

Tn = a + (n-1)d

= 1 + (n-1)*(-7)

= 1 -7n + 7

= 8 - 7n

User Ellbar
by
5.1k points